Pengaruh Jenis Pelarut Terhadap Aktivitas Antioksidan Ekstrak Cair Daun Turi (Sesbania grandiflora) - Gerald Masengi, Jevon Misael; Diah Puspawati, Gusti Ayu Kadek; Sri Wiadnyani, A.A. Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 2 (2020): Jurnal ITEPA, 2020)
The purpose of this study was to determine the effect of solvent types on antioxidant activity of turi (Sesbania grandiflora) leaves liquid extract and to determine the compatible solvent types which have the highest antioxidant activity of turi leaves liquid extract. The research used a completely randomized design with the treatment of solvent types consisting of 4 level which is: aquadest; acetone 70%; methanol 70%; and ethanol 70%. The treatment was repeated four times so that they were obtained 16 experiment units. The data was analyzed with analysis of variance and if the treatment had a significant effect followed by a Duncan's Multiple Range Test. The results showed the type of solvent treatment had a significant effect on antioxidant activity, total flavonoid, total tannin, and vitamin C content. The best treatment was obtained from turi leaves liquid extract using acetone 70% solvent which had the highest antioxidant activity of 75.71% with the value of IC50 269.67, total flavonoid 0.185 mg QE/g material, total tannin 0.013 mg TAE/g material and vitamin C content 0.45 mg AAE/ g material. Keywords : antioxidant activity, solvent types, turi leaves.